Parent and child relations in the perspective of adolescents with Juvenile delinquency - Nourmarifa Sari; Siti Rohmah Nurhayati (Department of Psychology, Universitas Negeri Yogyakarta, 2019)
This study aims to determine the relationship between parents and children in the perspective of adolescents with juvenile deliquency. This study uses qualitative methods with a phenomenological approach. The research subjects were two boys aged 16-20 years who had a delinquency scale score ≥17. In addition, the researcher uses the Theunnisen Delinquency Scale, as a deliquency scale, which has been translated and adjusted to the current conditions in Indonesia. As the result, it can be showed that relations according to adolescents with risky behavior were the existence of positive and negative relations. Positive relationships such as nurturing, transmitting values, closeness, attention, and togetherness. Negative relationships such as lack of support, lack of understanding, communication errors between parents and children, and conflicts that are not accompanied by good conflict management.